2013
DOI: 10.1371/journal.pone.0083458
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism of the Feto-Placental Phenotype in Response to a High Fat and Control Maternal Diets in a Rabbit Model

Abstract: Maternal environment during early developmental stages plays a seminal role in the establishment of adult phenotype. Using a rabbit model, we previously showed that feeding dams with a diet supplemented with 8% fat and 0.2% cholesterol (HH diet) from the prepubertal period and throughout gestation induced metabolic syndrome in adult offspring. Here, we examined the effects of the HH diet on feto-placental phenotype at 28 days post-coïtum (term = 31days) in relation to earlier effects in the blastocyst (Day 6).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
69
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(90 citation statements)
references
References 57 publications
4
69
1
5
Order By: Relevance
“…In this last study, the diet affected placental weight and placental efficiency regardless of the sex of the fetuses. In rabbits, a highfat diet before and throughout gestation induced high adiposity in the mothers, while their fetuses were of smaller weight, whereas placental efficiency remained unchanged (Tarrade et al, 2013). All these data demonstrate that variable results on fetal and placental weight have been reported, including a decrease or increase of weight or no effect, depending on species, diet composition and the time window of diet application.…”
Section: Feto-placental Weightmentioning
confidence: 73%
See 2 more Smart Citations
“…In this last study, the diet affected placental weight and placental efficiency regardless of the sex of the fetuses. In rabbits, a highfat diet before and throughout gestation induced high adiposity in the mothers, while their fetuses were of smaller weight, whereas placental efficiency remained unchanged (Tarrade et al, 2013). All these data demonstrate that variable results on fetal and placental weight have been reported, including a decrease or increase of weight or no effect, depending on species, diet composition and the time window of diet application.…”
Section: Feto-placental Weightmentioning
confidence: 73%
“…In contrast, fetuses displayed a dyslipidaemia that affected more males than females. Therefore, there was a physiological adaptation, with a relative protection of the female fetuses from developing dyslipidaemia (Tarrade et al, 2013). Finally, a recent study showed that maternal obesity in the mouse induced a reduction in placenta labyrinth thickness and cell proliferation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In rats, high-fat and high-salt diets lowered placental size of males, increasing the expression of genes associated with metabolism and pro-inflammatory mediators, which has been related to future cardiometabolic disturbances (Reynolds et al 2015). In rabbits, high-fat and high-cholesterol diets provoke higher accumulation of triacylglycerol in males while they upregulate genes of the lipid pathway in females (Tarrade et al 2013). In non-human primates, nutritional restriction has been reported to suppress genes related to programmed cell death and enhance genes associated with cell proliferation in female placentae.…”
Section: Placental Response To Maternal Dietmentioning
confidence: 99%
“…Une hyperthermie et une inflammation maternelle provoquée par une injection de lipopolysaccharide (LPS) juste après la fécondation [26], une sous-nutrition protéique durant la période pré-et/ou péricon-ceptionnelle, par exemple, peuvent perturber le développement chez la descendance, avec des différences en fonction du sexe [27,28]. Chez le lapin, une alimentation maternelle enrichie en lipides est associée à des changements d'expression de gènes dans l'embryon et à une accumulation de gouttelettes lipidiques dans le trophoblaste du blastocyste, retrouvée, en fin de gestation, dans le placenta (d'origine trophoblastique) [29]. Récemment, la notion de transmission paternelle, non génétique, de pathologies à long terme a émergé [30].…”
Section: Impact Des Biotechnologies De La Reproduction Sur La Santé Dunclassified